Karaite Mourning of Zion as an Ascetic Movement - Lasker, Daniel J. (Jewish Thought, 2021)
Karaite Judaism developed in an Islamic environment in which there were Muslim movements which preached asceticism (zuhd) as a religious value, perhaps in reaction to the temporal successes of early Islam. Their practice of asceticism included abstention in the areas of dress, food, drink, property, and sexual relations, in the hope of preparing the soul for the world to come in which the body would disintegrate and only the soul would remain. Among Rabbanite Jews, there were those who advocated an internal variety of zuhd, a sort of radical alienation from society, as a process of spiritual discipline. In the Land of Israel during the Golden Age of Karaism (end of the ninth-eleventh centuries), Karaites adopted ascetic practices (other than sexual abstinence), not in order to prepare the soul but as a way of bringing the Messiah. Those who adopted this ascetic way of life were referred to as the “Mourners of Zion.” There may have been Rabbanite Mourners (rabbinic literature mentions mourning customs in light of the destruction of the Temple), but the vast majority of the Mourners of Zion movement in the Land of Israel were Karaites. Since Karaite asceticism was mainly political, namely in the service of hastening redemption, one can assume that the Karaites would have been happy to leave behind their mourning customs if the messiah had come and rebuilt the Temple. In addition to asceticism for political purposes, there were Karaites who believed that one should adopt such practices without a direct connection to the mourning of Zion. The outstanding representative of this position was Salmon ben Yeruhim, who argued in his Commentary on Ecclesiastes that King Solomon taught asceticism for spiritual purposes and not just for political ones. In addition, Salmon claimed that in certain Psalms, King David described his own ascetic lifestyle. Since David and Solomon were not mourning for the Temple, their asceticism had no relation to its destruction and one should adopt their practices without regard for any political considerations. After the destruction of the Karaite community in the Land of Israel during the First Crusade, the Karaite center moved to Byzantium, where mourning was not perceived as an attractive lifestyle. The last known Karaite identified with the Mourners of Zion was the Byzantine Judah Hadassi the Mourner in the middle of the twelfth century. Until this very day, Karaites refrain from eating meat in Jerusalem as a way of remembering the Mourners of Zion movement.